Trümmer und Geräte der bei dem englischen Luftangriff auf Willemshaven abgeschossenen englischen schweren Bomber
Trümmer und Geräte der bei dem englischen Luftangriff auf Willemshaven abgeschossenen englischen schweren Bomber.